2005
DOI: 10.3168/jds.s0022-0302(05)72736-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Trans and Conjugated Fatty Acids and Bovine Milk Fat Yield Due to Dietary Concentrate and Linseed Oil

Abstract: Effects on fatty acid profiles and milk fat yield due to dietary concentrate and supplemental 18:3n-3 were evaluated in 4 lactating Holstein cows fed a low- (35:65 concentrate:forage; L) or high- (65:35; H) concentrate diet without (LC, HC) added oil or with linseed oil (LCO, HCO) at 3% of DM. A 4 x 4 Latin square with four 4-wk periods was used. Milk yield and dry matter intake averaged 26.7 and 20.2 kg/d, respectively, across treatments. Plasma acetate and beta-hydroxybutyrate decreased, whereas glucose, non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

77
296
11
14

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 255 publications
(398 citation statements)
references
References 34 publications
77
296
11
14
Order By: Relevance
“…Because of their lower proportion in milk fat and because of the lower milk fat production, the daily amount of short-chain FA was decreased with linseed diets: the total output of 8:0-14:0- saturated even-chain FA was 315, 258 and 211 g/day with diets C, RL and EL, respectively (P , 0.001 for both contrasts C v. linseed and RL v. EL), which represented a 18% and 33% decrease, respectively, and explained the reduction of milk fat yield. With raw linseed, Gonthier et al (2005) reported a 38% decrease of 8:0-14:0 daily output, and a 34% decrease was observed due to linseed oil (Loor et al, 2005). Similar effect was observed after soybean (Chouinard et al, 1997) or sunflower (Schingoethe et al, 1996) dietary addition.…”
Section: Conjugated Linoleic and Linolenic Acids In The Milk Of Cows supporting
confidence: 56%
See 3 more Smart Citations
“…Because of their lower proportion in milk fat and because of the lower milk fat production, the daily amount of short-chain FA was decreased with linseed diets: the total output of 8:0-14:0- saturated even-chain FA was 315, 258 and 211 g/day with diets C, RL and EL, respectively (P , 0.001 for both contrasts C v. linseed and RL v. EL), which represented a 18% and 33% decrease, respectively, and explained the reduction of milk fat yield. With raw linseed, Gonthier et al (2005) reported a 38% decrease of 8:0-14:0 daily output, and a 34% decrease was observed due to linseed oil (Loor et al, 2005). Similar effect was observed after soybean (Chouinard et al, 1997) or sunflower (Schingoethe et al, 1996) dietary addition.…”
Section: Conjugated Linoleic and Linolenic Acids In The Milk Of Cows supporting
confidence: 56%
“…Among possible reasons for this inhibition, Grummer (1991) cited a direct inhibition of mammary acetyl-CoA carboxylase, which is mediated by trans-10, cis-12 18:2 (Baumgard et al, 2000), but in our experiment, milk proportion of trans-10, cis-12 18:2 was very low with all diets. Loor et al (2005) suggested that milk fat depression could also be explained by other FA, including trans-10 18:1, which exhibited high proportions in milk with low proportions of 6:0-14:0 in our experiment. However, Lock et al (2007) recently demonstrated that this FA does not reduce milk fat synthesis in dairy cows.…”
Section: Conjugated Linoleic and Linolenic Acids In The Milk Of Cows mentioning
confidence: 50%
See 2 more Smart Citations
“…Breed 3 age interactions were considered significant at P < 0.10 to guard against type-II error. This was deemed appropriate because of the low number of experimental animals tested for interaction rather than main effects, and the a priori expectation on interactions (Loor et al, 2005).…”
Section: Methodsmentioning
confidence: 99%